Learning global journalism: A course on journalism on developing countries in Africa and the Finnish freelance journalism market - Hujanen, Jaana (Žurnalistikos tyrimai, 2009)
A group of Finnish journalism students travelled to Zambia, Africa in November 2007. The field trip was a culmination for a course in journalism on developing  countries. The starting points reflected the practices and models of the research-based approach to learning. The role of the students was twofold: they were students as well as journalists. The aims were, to deepen the students’ understanding of current issues in developing countries, their visibility and treatment in the media and of actors in development cooperation and to produce journalism on developing countries for the domestic media. In this article, first, the students’ views on what they consider as good  journalism on developing countries, based on the observations they made during their trip, is analysed. Secondly, the students’  experiences on what they learned about journalism practices on developing countries during their writing processes are analysed, and also their observations on the ideals and practices of freelance journalism when selling their own stories. The data analysed includes participant-observation from the field trip in Zambia and qualitative research interviews conducted with the students after the trip. The article highlights the importance of students’ own role in directing their field work, involving goal setting, questioning and self-evaluation of the knowledge gained. It also sheds light on how research and experience-based learning in a developing country and an unfamiliar culture can contribute to a comprehensive way of learning. In this case alternative ideas how issues about developing countries could be evaluated and represented in western local and national media.